Cost-effectiveness analysis of patient-specific and standard vertebral body replacements in the surgical treatment of spinal tumors - Nikita S. Zaborovskii; Sergei V. Masevnin; Dmitrii A. Ptashnikov; Rashid M. Tikhilov (Traumatology and Orthopedics of Russia, 2026)
Abstract Background. The widespread integration of patient-specific vertebral body prostheses is hindered by their high manufacturing costs. A comprehensive understanding of the long-term cost-effectiveness of additive manufacturing is required for informed decision-making in spine surgery. Objective. To evaluate the cost-effectiveness of patient-specific 3D-printed polyetheretherketone (3D PEEK) prostheses compared to off-the-shelf constructs for anterior spinal column reconstruction in patients with spinal tumors. Methods. A retrospective cohort study was conducted on 85 patients who underwent spinal surgery between 2018 and 2025 (34 in the 3D PEEK group, 51 in the standard group). We assessed clinical profiles, perioperative parameters, survival rates, complication frequencies, and quality of life (EQ-5D-5L). A health economic evaluation was performed using a Markov model (60-month horizon, 1-month cycle, 3% discount rate). Cost-effectiveness was determined based on the incremental cost-effectiveness ratio (ICER) against a willingness-to-pay (WTP) threshold of 2,235,202 RUB/QALY. Results. Both cohorts were comparable in baseline demographics and clinical characteristics. The revision rate was significantly lower in the 3D PEEK group (12% vs. 33%, p=0.024). Both groups demonstrated improved quality of life, but the utility gain was more pronounced with customized implants: the final utility index reached 0.718±0.122 vs. 0.611±0.155 (p=0.004). Direct primary medical costs were predictably higher for the 3D PEEK cohort (489,361 RUB vs. 269,950 RUB, p0.001). Markov modeling indicated that the 3D PEEK strategy required an additional 161,661 RUB while yielding an extra 0.298 QALY. The ICER was calculated at 541,873 RUB/QALY, remaining well below the established WTP threshold. Probabilistic sensitivity analysis confirmed a median ICER of 368,357 RUB/QALY. Conclusion. The application of patient-specific 3D PEEK prostheses in spinal oncology is a highly cost-effective strategy. Despite elevated initial fabrication costs, enhanced biomechanical stability and the consequent reduction in revision surgeries facilitate long-term preservation of patient quality of life.